Condition monitoring in vehicle cabin using vibration signal characterization - Muhammad Naufal Mansor
This paper presents an approach to the condition monitoring in vehicle. A vibration test profiles is obtained in road testing of sedan sized car. The first step is to define the performance parameters under study.